Ethical leadership, trust in leader and creativity: The mediated mechanism and an interacting effect. (15th February 2018) - Javed, Basharat; Rawwas, Mohammed Y A; Khandai, Sujata; Shahid, Kamran; Tayyeb, Hafiz Habib
Abstract: This study examines the relationship between ethical leadership and employee creativity with mediating role of trust in leader and moderating role of openness to experience. Data were collected from 205 supervisor–subordinate small textile firms across Pakistan. Confirmatory factor analysis confirmed the distinctiveness of variables used in our study. The results confirmed that ethical leadership promotes creativity at workplace, while trust in leader mediates the effect of ethical leadership on creativity. Furthermore, the results did not confirm the moderation of openness to experience on the relationship between trust in leader and employee creativity. The implications are discussed.